2011
DOI: 10.1109/ted.2011.2164615
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Bipolar and Complementary Resistive Switching Memory Based on Amorphous Carbon

Abstract: Abstract-There has been a strong demand for developing an ultradense and low-power nonvolatile memory technology. In this paper, we present a carbon-based resistive random access memory device with a carbon nanotube (CNT) electrode. An amorphous carbon layer is sandwiched between the fast-diffusing top metal electrode and the bottom CNT electrode, exhibiting a bipolar switching behavior. The use of the CNT electrode can substantially reduce the size of the active device area. We also demonstrate a carbon-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 41 publications
2
48
0
Order By: Relevance
“…3,4 Till now, a large number of ECM cells have been reported, employing various insulating materials such as chalcogenides, [5][6][7][8][9][10][11][12][13] oxides, [14][15][16][17][18][19][20][21][22][23][24] amorphous Si (Refs. 25 and 26) and C, [27][28][29][30] and organic materials. 31,32 For the RS mechanism of ECM cells, the most widely accepted hypothesis is as follows, 1-3 with Cu as the AE (anode) and Pt as the CE (cathode) metal: (i) anodic dissolution of Cu; (ii) drift of the Cu ions across the insulator film; (iii) reduction and electro-crystallization of Cu on the CE surface, leading to the formation of a conical filament with the base and the tip located at the cathodic and the anodic interfaces, and switching the cell ON; (iv) electrochemical dissolution at the weakest point along the length of the filament, i.e., near the anodic interface as a sufficient opposite polarity voltage is applied, switching the cell OFF.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Till now, a large number of ECM cells have been reported, employing various insulating materials such as chalcogenides, [5][6][7][8][9][10][11][12][13] oxides, [14][15][16][17][18][19][20][21][22][23][24] amorphous Si (Refs. 25 and 26) and C, [27][28][29][30] and organic materials. 31,32 For the RS mechanism of ECM cells, the most widely accepted hypothesis is as follows, 1-3 with Cu as the AE (anode) and Pt as the CE (cathode) metal: (i) anodic dissolution of Cu; (ii) drift of the Cu ions across the insulator film; (iii) reduction and electro-crystallization of Cu on the CE surface, leading to the formation of a conical filament with the base and the tip located at the cathodic and the anodic interfaces, and switching the cell ON; (iv) electrochemical dissolution at the weakest point along the length of the filament, i.e., near the anodic interface as a sufficient opposite polarity voltage is applied, switching the cell OFF.…”
Section: Introductionmentioning
confidence: 99%
“…A non-destructive readout method based on capacitive voltage divider was also proposed [69]. CRS has been demonstrated in different resistive switching devices, for example, Cu/SiO 2 /Pt bipolar resistive switches [70], amorphous carbon-based RRAM [71], TaO x -based RRAM [72][73][74], multi-layer TiO x device [75], HfO x RRAM [76], ZrO x /HfO x bi-layer RRAM [77], Cu/TaO 2 atomic switch [78], Nb 2 O 5 x /NbO y RRAM [79], and so on. An important issue with CRS is the "ON window."…”
Section: Complementary Resistive Switchmentioning
confidence: 99%
“…It has been confirmed that one CRS exhibits the superimposed current-voltage (I-V) properties of two bipolar resistive switching cells, namely complementary switching (CS). The sneak current problem of crossbar arrays can be effectively suppressed without the extra selection elements by programming one switch of CRS to be the high resistance state (HRS), and another to be the low resistance state (LRS) alternately [2][3][4]. To avoid the delicate fabrication processes and the possible degradation of active common internal electrode of this CRS [5,6], many efforts were focus to fabricate RRAM with CS based on oxide heterostructure, including Ta 2 O 5Àx /TiO y [6], TiO 2Àx /TiN x O y [7] bilayer geometry, TiO x/ TiO y /TiO x and TiO x /TiON/TiO x triple-layer structure [8].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the ultra-dense memories, RRAM was expected to be integrated in the passive crossbar arrays. However, a great challenge arises due to the crosstalk issue resulted from the parasitic sneak current paths around the neighboring crossbar cells [1][2][3]. Recently, a complementary resistive switches (CRS) consisting of two anti-serial bipolar RRAM cells by sharing an internal electrode has been proposed to solve this crosstalk issue [1].…”
mentioning
confidence: 99%